An Overview Of Aesthetics In The Select Verses Of Bhrathiyar And Vairamuthu - J.M. Gracelin Lydia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Crafting of beauty is tapas and the artist who crafts it is a yogi and there is no hiatus between the mundane and the divine. The wafer-thin line between the gross and the subtle gets blurred raising one to the level of yogi. This paper entitled “An Overview of Aesthetics in the Select Verses of Bharathiyar and Vairamuthu”, gives a bird’s eye view and delineates how a heightened form of perception and sensitivity is needed to enter into aesthetic rapture. Aesthetics is a branch of philosophy and it is closely associated with art. As a science it is the science of perceptible forms and accounts for nature, source, purpose and creative process of art.